2018
DOI: 10.1063/1.5047808
|View full text |Cite|
|
Sign up to set email alerts
|

Defect identification based on first-principles calculations for deep level transient spectroscopy

Abstract: Deep level transient spectroscopy (DLTS) is used extensively to study defects in semiconductors. We demonstrate that great care should be exercised in interpreting activation energies extracted from DLTS as ionization energies. We show how first-principles calculations of thermodynamic transition levels, temperature effects of ionization energies, and nonradiative capture coefficients can be used to accurately determine actual activation energies that can be directly compared with DLTS. Our analysis is illustr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…3. A recent study found that variation of ionization energies with temperature can cause disparities between defect transition levels and the actual likely activation energies seen in experimental DLTS studies in GaN (highly dependent on the defect itselffor 300 K, a variation of $60 meV was seen for V Ga -O N -2H, while a signicant $250 meV shi was seen for C N ), 31 and as such this agreement between our simulations and DLTS could be fortuitous. In both prior, PBE-based defect studies of Sb 2 Se 3 , however, no transition levels align well with these DLTS levels, even considering a large temperature effect (neither study gives a possible hole trap within 0.3 eV of the 0.71 eV hole trap position, and the closest transition levels are at least 0.1 eV from the rst hole trap)this does seem to demonstrate the necessity for a hybrid functional, as well as a comprehensive study of all possible charge states to properly describe the material's complex defect chemistry.…”
Section: Resultssupporting
confidence: 79%
“…3. A recent study found that variation of ionization energies with temperature can cause disparities between defect transition levels and the actual likely activation energies seen in experimental DLTS studies in GaN (highly dependent on the defect itselffor 300 K, a variation of $60 meV was seen for V Ga -O N -2H, while a signicant $250 meV shi was seen for C N ), 31 and as such this agreement between our simulations and DLTS could be fortuitous. In both prior, PBE-based defect studies of Sb 2 Se 3 , however, no transition levels align well with these DLTS levels, even considering a large temperature effect (neither study gives a possible hole trap within 0.3 eV of the 0.71 eV hole trap position, and the closest transition levels are at least 0.1 eV from the rst hole trap)this does seem to demonstrate the necessity for a hybrid functional, as well as a comprehensive study of all possible charge states to properly describe the material's complex defect chemistry.…”
Section: Resultssupporting
confidence: 79%
“…An upper estimate for this barrier can be obtained by constructing a one-dimensional configuration coordinate diagram for the transition, as explained in refs. 37,38 , i.e., the activation energies for V Si observed by DLTS are predicted to occur within the highlighted ranges in Fig. 3.…”
Section: Identifying Charge State Transitions Of the Silicon Vacancymentioning
confidence: 80%
“…First‐principles calculations predict a barrier δE ≈ 0.49 eV for the capture of holes by the C N acceptor. [ 50 ] As a result, the C p i is expected to increase by two orders of magnitude as the temperature increases from 20 to 600 K. This prediction contradicts the experimental data. Indeed, according to Equation (), the PL intensity before its quenching is proportional to the C p i , and no variation of PL intensity with temperature can be noticed for the YL1 band (Figure 2).…”
Section: Peculiarities Of Thermal Quenching Of Pl In Ganmentioning
confidence: 93%